Exonuclease domain mutants of yeast DIS3 display genome instability. (1st January 2019) - Milbury, Karissa L.; Paul, Biplab; Lari, Azra; Fowler, Claire; Montpetit, Ben; Stirling, Peter C.
ABSTRACT: The exosome functions to regulate the cellular transcriptome through RNA biogenesis, surveillance, and decay. Mutations in Dis3, a catalytic subunit of the RNA exosome with separable endonuclease and exonuclease activities, are linked to multiple myeloma. Here we report that a cancer-associated DIS3 allele, dis3 E729K, provides evidence for DIS3 functioning in mitotic fidelity in yeast. This dis3 E729K allele does not induce defects in 7S→5.8S rRNA processing, although it elicits a requirement for P-body function. While it does not significantly influence cell cycle progression alone, the allele reduces the efficiency of cell cycle arrest in strains with defects in kinetochore assembly. Finally, point mutations in the exonuclease domains of yeast Dis3 elicit genome instability phenotypes; however, these DIS3 mutations do not increase DNA damage or RNA processing defects that lead to the accumulation of polyadenylated RNA in the nucleus. These data suggest that specific DIS3 activities support mitotic fidelity in yeast.